الاستجابة المتفوقة لحاجات العملاء....ضرورة أم خيار - بوزورين, فيروز (Recherches économiques et managériales; Vol. 12 No 01 (2018): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES(Décembre), 2020)
تهدف هذه الدراسة إلى معرفة مدى قدرة المؤسسات على تحقيق الاستجابة المتفوقة لحاجات العملاء، وذلك من خلال الإنتاج حسب الطلب لمقابلة الاحتياجات الخاصة للعميل والاستجابة السريعة لطلباته مع تحقيق مستوى الجودة المطلوب، وهل أن ذلك يُعتبر ضرورة أم خيارا. ولتحقيق هذا الهدف، تم القيام بدراسة تطبيقية على مجموعة من المؤسسات المتوسطة الحجم بولاية سطيف بالاعتماد على الاستمارة  كأداة أساسية لجمع البيانات. خلصت الدراسة إلى أن: هذه المؤسسات تضع العميل في مقدمة اهتماماتها، وأنها تقوم بالاتصال بالعملاء للتعرف على ميولاتهم واتجاهاتهم في الطلب المرتقب على منتجاتها، وأنها تقوم بإنتاج منتجات وتقديم خدمات حسب طلب العملاء، وأنها تحقق الاستجابة السريعة لطلباتهم، مما يؤدي إلى تنمية الولاء والانتماء للمؤسسة. الكلمات المفتاحية: العميل؛ خدمة العميل؛ الاستجابة المتفوقة لحاجات العميل؛ الإنتاج حسب الطلب؛ وقت الاستجابة. Abstract : The objective of this study is to identify the extent to which institutions can achieve superior customer needs, through customized production to meet the specific needs of the customer and respond quickly to its demands while achieving the required quality level, and is this a necessity or a choice. To achieve this objective, an applied study was conducted on a group of medium-sized enterprises in Setif drawing on the questionnaire as an essential tool for data collection. The study concluded that: These institutions put the customer at the forefront of their concerns, and that they contact customers to identify their tendencies and trends in the expected demand for their products, and they produce products and provide services as per customer request, and they achieve rapid response to their requests, which leads to the development of loyalty and belonging to the institution. Key words : Customer; Customer Service; Superior Response to Customer Needs; Production on demand; response time.